SPILLOVER EFFECT PENGANGGURAN TERBUKA INDONESIA - Marsono (Journal of Innovation Research and Knowledge, 2021)
This study aims to model the variable percentage of young people (15-24 years) who are not in school, working or participating in training, the proportion of informal employment in the non-agricultural sector, economic growth, Provincial Minimum Wages (UMP), and realization of investment in capital. unemployment. In addition, estimating the direct effect and spillover effect of the independent variables on unemployment. Panel data spatial model built in this study is a durbine spatial model with spatial and time fixed effects using two spatial weights, namely rook contiguity and customize weights. Based on the unemployment model with the spatial durbine model in spatial conditions and time fixed effects, it shows that the variables that have a significant effect (α=5%) on Indonesian unemployment are the unemployment rate in other regions, the percentage of young people (15-24 years) who are not in school, working. or attend training and economic growth